Soil Moisture Characteristics on Several Soil Types - Dwi Putro Tejo Baskoro; Suria Darma Tarigan (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
Soil water availability is one of the important factors injluencing plant growth. Soil that can store more water in alonger time can support a better plant growth. This study was aimed to evaluate the dynamics of soil water of four differentsoils with different characteristics. Four soils classes are clayey textured soils-Red Yellowish Podsolik Jasinga, Clayeytextured soils-Latosol Darmaga, . Sandy Textured soil-Regosol Sindang Barang, and highly organic mater content soi/sAndosolSukamantri. The result showed that at every-suction analyzed, Andosol Sukamantri had consistently highest watercontent while Regosol Sindang Barang was consistently lowest. Similar tendency wasfoundfor available water capacity. Theresult also showed that moisture content at Regosol decrease more rapidly than those of the other three soils. The time need to reach likely constant moisture content is variable with soil type; lowest at Regosol Sindangbarang (45 hours after completely saturated and drained) followed by Podsolik Jasinga (73 hours), Latosol darmaga (74 hours) and Andosol Sulcamatri (76 hours).